2023
DOI: 10.31857/s0026898423010020
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-11 in Pathology of the Nervous System

Abstract: The study of the role of cytokines in various pathological conditions of the body is one of the topical areas of modern biomedicine. Interleukin 11 (IL-11) was discovered in 1990 in fibrocyte-like bone marrow stromal cells, but there has been an increased interest in the cytokine in recent years. The cytokine plays a significant role in the central nervous system; local expression of this cytokine by nerve cells has been shown. Studies show the involvement of IL-11 in the mechanisms of development of a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…IL-11 has important roles in inflammation, fibrosis, and carcinoma, allowing the development of novel therapeutics with the potential for clinical targeting of IL-11 signaling in multiple diseases. 42 , 43 Studies were performed to define the IL-11 regulation by viruses and its implications for viral pathogenesis. It has been previously demonstrated that up-regulation of IL-11 was observed at 72 h post-infection of cCyprinid herpesvirus.…”
Section: Discussionmentioning
confidence: 99%
“…IL-11 has important roles in inflammation, fibrosis, and carcinoma, allowing the development of novel therapeutics with the potential for clinical targeting of IL-11 signaling in multiple diseases. 42 , 43 Studies were performed to define the IL-11 regulation by viruses and its implications for viral pathogenesis. It has been previously demonstrated that up-regulation of IL-11 was observed at 72 h post-infection of cCyprinid herpesvirus.…”
Section: Discussionmentioning
confidence: 99%